Quality of Online Pharmacies and Websites Selling Prescription Drugs: A Systematic Review - Orizio, Grazia; Merla, Anna; Schulz, Peter J; Gelatti, Umberto (JMIR Publications, 2011)
BackgroundOnline pharmacies are companies that sell pharmaceutical preparations, including prescription-only drugs, on the Internet. Very little is known about this phenomenon because many online pharmacies operate from remote countries, where legal bases and business practices are largely inaccessible to international research. ObjectiveThe aim of the study was to perform an up-to-date and comprehensive review of the scientific literature focusing on the broader picture of online pharmacies by scanning several scientific and institutional databases, with no publication time limits. MethodsWe searched 4 electronic databases up to January 2011 and the gray literature on the Internet using the Google search engine and its tool Google Scholar. We also investigated the official websites of institutional agencies (World Health Organization, and US and European centers for disease control and drug regulation authorities). We focused specifically on online pharmacies offering prescription-only drugs. We decided to analyze and report only articles with original data, in order to review all the available data regarding online pharmacies and their usage. ResultsWe selected 193 relevant articles: 76 articles with original data, and 117 articles without original data (editorials, regulation articles, or the like) including 5 reviews. The articles with original data cover samples of online pharmacies in 47 cases, online drug purchases in 13, consumer characteristics in 15, and case reports on adverse effects of online drugs in 12. The studies show that random samples with no specific limits to prescription requirements found that at least some websites sold drugs without a prescription and that an online questionnaire was a frequent tool to replace prescription. Data about geographical characteristics show that this information can be concealed in many websites. The analysis of drug offer showed that online a consumer can get virtually everything. Regarding quality of drugs, researchers very often found inappropriate packaging and labeling, whereas the chemical composition usually was not as expected in a minority of the studies' samples. Regarding consumers, the majority of studies found that not more than 6% of the samples had bought drugs online. ConclusionsOnline pharmacies are an important phenomenon that is continuing to spread, despite partial regulation, due to intrinsic difficulties linked to the impalpable and evanescent nature of the Web and its global dimension. To enhance the benefits and minimize the risks of online pharmacies, a 2-level approach could be adopted. The first level should focus on policy, with laws regulating the phenomenon at an international level. The second level needs to focus on the individual. This approach should aim to increase health literacy, required for making appropriate health choices, recognizing risks and making the most of the multitude of opportunities offered by the world of medicine 2.0.